Relationship between soil apparent electrical conductivity with nitrogen and CEC in oil palm plantation - Mohd Husin, Ezrin; Wayayok, Aimrun; Bejo, Siti Khairunniza; Abdullah, A. F. (Faculty of Engineering, Universiti Putra Malaysia, 2018)
Soil electrical conductivity (ECa) sensor had been widely used in precision farming in identify the soil variability such of its nutrient requirement and soil productivity. In oil palm industry, nitrogen fertilizer and other nutrients are usually broadcast uniformly throughout a field. Site-specific management can be developed through understanding the relationship between sensor measurement and soil properties. This study was conduct in order to determine the relationship between soil ECa with Nitrogen (N) and Cation Exchange Capacity (CEC) in oil palm plantation at Jawa Series. The soil samples were collected at three different depths; 0-15cm, 15-30cm and 30-45 cm respectively. The study showed that both nitrogen and CEC had significant negative correlation with shallow ECa at all three different depths. From the results, the soil variability map has been produced as a reference for oil palm plantation management.